HUBUNGAN ANTARA PERILAKU PEMBERANTASAN SARANG NYAMUK (PSN) DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) - Setyo Dwi Widyastuti (JURNAL KESEHATAN INDRA HUSADA, 2022)
HF in Indonesia in 2019 was 51.48 per 100,000 population, an increase from two years ago, namely 2016 and 2017 when the DHF incidence rate (IR) was 26.1 and 24.75 per 100,000 population. . Based on the case fatality rate (CFR), it seems to have decreased slightly from 0.71% in 2018 to 0.67% in 2019. The purpose of this study was to determine the relationship between mosquito nest eradication behavior (PSN) and the incidence of dengue hemorrhagic fever (DHF). The type of research used is a literature review with a systematic literature review method, the number of articles reviewed is 5 articles , the process of analyzing articles with techniques for finding similarities, providing views, comparing, and summarizing. The result of this study is that there is a relationship between mosquito nest eradication behavior (PSN) and the incidence of dengue hemorrhagic fever (DHF). The existence of a relationship can be seen from several studies which state that many family heads do not carry out PSN properly. The conclusion of this study is that there is a significant relationship between PSN behavior and the incidence of DHF. So the head of the family is expected to be able to set an role model for his family to carry out behavior in eradicating mosquito nests properly so as to reduce the incidence of DHF.